2012
DOI: 10.1098/rsbl.2012.0125
|View full text |Cite
|
Sign up to set email alerts
|

Niche-based mechanisms operating within extreme habitats: a case study of subterranean amphipod communities

Abstract: It has been suggested that both niche-based and neutral mechanisms are important for biological communities to evolve and persist. For communities in extreme and isolated environments such as caves, theoretical and empirical considerations (low species turnover, high stress, strong convergence owing to strong directional selection) predict neutral mechanisms and functional equivalence of species. We tested this prediction using subterranean amphipod communities from caves and interstitial groundwater. Contrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Species adapted to the subterranean environment often encounter each other. This co‐occurrence of two or more, often closely related, species has been commonly observed at different spatial scales, even within the same compartment of a single cave (Fišer et al , Trontelj et al , Vergnon et al ). In such a resource‐limited environment, co‐occurring conspecific and heterospecific individuals are likely to compete for resources.…”
Section: Introductionmentioning
confidence: 83%
“…Species adapted to the subterranean environment often encounter each other. This co‐occurrence of two or more, often closely related, species has been commonly observed at different spatial scales, even within the same compartment of a single cave (Fišer et al , Trontelj et al , Vergnon et al ). In such a resource‐limited environment, co‐occurring conspecific and heterospecific individuals are likely to compete for resources.…”
Section: Introductionmentioning
confidence: 83%
“…Despite their potential utility as models to study these topics, subterranean organisms, including spiders, have only rarely been used as models for the study and definition of the ecological niche (see, e.g., Fišer et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the richness of groundwater crustaceans increased monotonically with habitat heterogeneity as represented by the number and relative proportion of distinct habitat types with characteristic flow conditions (permeability) and pore size. Trontelj et al () found clear evidence of divergent morphological adaptations among closely related species of amphipods that use different cave microhabitats with distinct flow velocity (but see also Fišer et al ). A similar process of divergent selection may in part account for a positive richness–habitat heterogeneity relationship at a continental scale, because it allows more species to co‐exist in regions characterized by a high diversity of aquifers in unconsolidated sediments and consolidated rock (Cornu et al ).…”
Section: Discussionmentioning
confidence: 99%